Biomimetic insulin-imprinted polymer nanoparticles as a potential oral drug delivery system - Paul Pijush Kumar; Treetong Alongkot; Suedee Roongnapa (Acta Pharmaceutica)
In this study, we investigate molecularly imprinted polymers (MIPs), which form a three-dimensional image of the region at and around the active binding sites of pharmaceutically active insulin or are analogous to b cells bound to insulin. This approach was employed to create a welldefined structure within the nanospace cavities that make up functional monomers by cross-linking. The obtained MIPs exhibited a high adsorption capacity for the target insulin, which showed a significantly higher release of insulin in solution at pH 7.4 than at pH 1.2. In vivo studies on diabetic Wistar rats showed that the fast onset within 2 h is similar to subcutaneous injection with a maximum at 4 h, giving an engaged function responsible for the duration of glucose reduction for up to 24 h. These MIPs, prepared as nanosized material, may open a new horizon for oral insulin delivery.